Coping methods of college students with different personality traits when facing COVID-19 from the anxiety psychology perspective - Fu, Hai; Mao, Yuyao; Tian, Li (Frontiers in Psychology, 2024)
Objective Based on a survey of anxiety among college students during the epidemic, this study takes anxiety as an example to study the coping methods of college students with different personality traits. Thus predicting the behavioral tendencies of college students and proposing some appropriate suggestions for the current psychological education work of college students. Method: The study was carried out during the large-scale outbreak of the COVID-19 epidemic, and the investigation lasted one month. Using the Self Rating Anxiety Scale (SAS), Eysenck Personality Questionnaire Simplified Chinese Version (EPQ-RSC), and Trait Coping Style Scale (TCSQ), an online questionnaire survey was conducted on 932 college students to analyze the mutual effects of different grades, genders, personality traits, coping methods, and other factors. Results The research found that there was a significant gender difference in negative coping methods and anxiety among college students. Grade differences: In the comparative study of personality traits, there are gender differences in introversion and concealment dimensions and grade differences in neuroticism and concealment dimensions. There is a pairwise correlation between personality traits, coping methods, and anxiety. There is a significant positive correlation between the dimensions of psychoticism, neuroticism and anxiety; There is a significant negative correlation between introversion, concealment, and anxiety. Positive coping methods are significantly negatively correlated with anxiety, while negative coping methods are significantly positively correlated with anxiety. The positive coping style is significantly negatively correlated with the dimensions of psychoticism and neuroticism and positively correlated with the dimensions of introversion, introversion, and concealment; Negative coping methods are significantly positively correlated with the dimensions of psychoticism and neuroticism and negatively correlated with the dimensions of introversion, introversion, and concealment. Conclusion The research results indicate that the mental health issues of college students need to be taken seriously to prevent the spread of anxiety.